Improved referral and survival of newborns after scaling up of intensive care in Suriname - Rens Zonneveld; Natanael Holband; Anna Bertolini; Francesca Bardi; Neirude P. A. Lissone; Peter H. Dijk; Frans B. Plötz; Amadu Juliana (BMC, 2017)
Abstract Background Scaling up neonatal care facilities in developing countries can improve survival of newborns. Recently, the only tertiary neonatal care facility in Suriname transitioned to a modern environment in which interventions to improve intensive care were performed. This study evaluates impact of this transition on referral pattern and outcomes of newborns. Methods A retrospective chart study amongst newborns admitted to the facility was performed and outcomes of newborns between two 9-month periods before and after the transition in March 2015 were compared. Results After the transition more intensive care was delivered (RR 1.23; 95% CI 1.07-1.42) and more outborn newborns were treated (RR 2.02; 95% CI 1.39-2.95) with similar birth weight in both periods (P=0.16). Mortality of inborn and outborn newborns was reduced (RR 0.62; 95% CI 0.41-0.94), along with mortality of sepsis (RR 0.37; 95% CI 0.17-0.81) and asphyxia (RR 0.21; 95% CI 0.51-0.87). Mortality of newborns with a birth weight <1000 grams (34.8%; RR 0.90; 95% CI 0.43-1.90) and incidence of sepsis (38.8%, 95% CI 33.3-44.6) and necrotizing enterocolitis (NEC) (12.5%, 95% CI 6.2-23.6) remained high after the transition. Conclusions After scaling up intensive care at our neonatal care facility more outborn newborns were admitted and survival improved for both in- and outborn newborns. Challenges ahead are sustainability, further improvement of tertiary function, and prevention of NEC and sepsis.